TL15 of Arthrospira platensis sulphite reductase scavenges free radicals demonstrated in oxidant induced larval zebrafish Danio rerio model - Sarkar, Purabi; Lite, Christy; Kumar I, Praveen; Pasupuleti, Mukesh; N. T., Saraswathi; Arasu, Mariadhas Valan; Al-Dhabi, Naif Abdullah; Arshad, Aziz; Arockiaraj, Jesu (Elsevier, 2021)
The antioxidant role of sulfite reductase (SiR) derived from Arthrospira platensis (Ap) was identified through a short peptide, TL15. The study showed that the expression of ApSiR was highly expressed on day ten due to sulfur deprived stress in Ap culture. TL15 peptide exhibited strong antioxidant activity when evaluated using antioxidant assays in a concentration ranging from 7.8 and 125 μM. Further, the cytotoxicity of TL15 peptide was investigated, even at the higher concentration (250 μM), TL15 did not exhibit any toxicity, when tested in vitro using human leucocytes. Moreover, a potential reduction in reactive oxygen species (ROS) production was observed due to the treatment of TL15 peptide (>15.6 μM) to H2O2 exposed leucocytes. For the in vivo assessment of TL15 toxicity and antioxidant ability, experiments were performed in zebrafish (Danio rerio) larvae to analyse the developmental toxicity of TL15 peptide. Results showed that, exposure to TL15 peptide in tested concentrations ranging from 10, 20, 40, and 80 μM, did not affect the development and physiological parameters of the zebrafish embryo/larvae such as morphology, survival, hatching and heart rate. Fluorescent assay was performed using DCFH-DA (2,7-dichlorodihydrofluorescein diacetate) to examine the production of intracellular reactive oxygen species (ROS) in zebrafish treated with TL15 peptide during the embryo-larval stages. Fluorescent images showed that pre-treatment with TL15 peptide to attenuate the H2O2 induced ROS levels in the zebrafish larvae in a dose-dependent manner. Further to uncover the underlying biochemical and antioxidant mechanism, the enzyme activity of superoxide dismutase (SOD), catalase (CAT) and lipid peroxidation (LPO) levels were studied in zebrafish larvae. TL15 pre-treated groups showed enhanced antioxidant enzyme activity, while the hydrogen peroxide (H2O2) exposed larvae showed significantly diminished activity. Overall results from the study revealed that, TL15 act as a potential antioxidant molecule with dose-specific antioxidant property. Thus, TL15 peptide could be an effective and promising source for biopharmaceutical applications.